Menghini, R y Negrin M. (comps.) - Aguirre, Jonathan (Praxis Educativa, 2015)
Menghini, R y Negrin M. (comps.) <span style="font-size: 11.0pt; line-height: 115%; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: ES; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Docentes principiantes. Aventuras y desventuras de los inicios en la enseñanza